AL-QUR'AN INSIGHTS ON WORK ETHICS - K, Ratna.; Haddade, Hasyim (Ma'had Aly As'adiyah Sengkang, 2024)
This article aims to find out the meaning of work ethic and the verses of the Qur'an that describe it, and the relevance of verses about work ethic in increasing the work productivity of Muslims. In Islam, a Muslim is a worker. The deep belief that work is a way to demonstrate good deeds as well as a means of glorification is the basis of the Muslim work ethic. Muslims are also taught to strive for a balance between material success in this world and the afterlife. A Muslim who works to worship Allah must sincerely remember His rights and obey moral laws. It is hoped that the application of religious precepts in everyday life will increase the level of welfare as stated in the Al-Qur'an and Sunnah. A Muslim is taught a strong work ethic so that he can serve Allah and live a better life. Additionally, Muslims must face the free market times and struggle to survive and earn a respectable life based on their extraordinary talents and work ethic. A literature review or literature research methodology was used to write this article. From the results of the discussion, it was discovered that the Qur'an contains many verses about work ethics, one of which requires humans to work to manage the land and improve its welfare. Tauhid has a strong work ethic because he is the main worker. Although the section on work ethics has many benefits in helping Muslims be more productive at work, the reality is very different from what one might think.